Improving the Productivity of Beef Heifers in Florida - Phillip Lancaster; Chris Prevatt; John Arthington (EDIS)
Beef replacement heifers are a necessary but costly part of every cow-calf operation. A decision needs to be made to either purchase replacement heifers or raise them on the ranch. This is a long-term decision that will affect the ranch for many years through the genetics of the replacement heifers and through equipment and management inputs. This revised 9-page fact sheet provides an analysis of considerations for raising replacements; factors to consider in selection; and recommendations for nutritional management. Written by Phillip Lancaster, Chris Prevatt, and John Arthington, and published by the UF Department of Animal Sciences, March 2015. (Photo: Beef Improvement Federation)